2008
DOI: 10.4018/jiit.2008010104
|View full text |Cite
|
Sign up to set email alerts
|

Agile Workflow Technology and Case-Based Change Reuse for Long-Term Processes

Abstract: The increasing dynamics of today's work impacts the business processes. Agile workflow technology is a means for the automation of adaptable processes. However, the modification of workflows is a difficult task that is performed by human experts. This article discusses the novel approach of agile workflow technology for dynamic, long-term scenarios and on change reuse. First, it introduces new concepts for a workflow modeling language and enactment service, which enable an interlocked modeling and execution of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(43 citation statements)
references
References 29 publications
0
43
0
Order By: Relevance
“…From the technical viewpoint, as observed in section 2, the graph edit distance measure, that we have adapted in this work, was originally resorted to in [14]. However, with respect to that approach, by focusing just on traces of execution we did not need to consider extensions to the similarity measure able to deal with control flow elements (such as alternatives and iterations).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…From the technical viewpoint, as observed in section 2, the graph edit distance measure, that we have adapted in this work, was originally resorted to in [14]. However, with respect to that approach, by focusing just on traces of execution we did not need to consider extensions to the similarity measure able to deal with control flow elements (such as alternatives and iterations).…”
Section: Discussionmentioning
confidence: 99%
“…For the same reason, we did not insert any penalty for pairs of arcs in different traces with a different input or output action, which is already accounted for by the comparison between pairs of actions themselves. On the other hand, when focusing on linear traces our approach is more general and flexible than the one in [14]. As a matter of fact, we resort to taxonomical knowledge for comparing pairs of actions, so that two different actions do not always have a zero similarity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are various reasons why exceptions occasionally occur that necessitate such changes [80]. Interestingly, a study of processes in the chip design industry [51] found that actual in-stance changes are often highly similar. This has been confirmed in other domains like healthcare, e-negotiation, and transportation [97].…”
Section: Pms6: Unused Branches (Unused Code In Se)mentioning
confidence: 99%